Anisotropic Diffusion of Charges on Au Nanoclusters Embedded in Al2O3 Dielectrics - Park, Jinhong; Choi, Jinhyeok; Choi, Moonkang; Ryu, Hyunyeol; Ryu, Hanyoul; Lee, Hyungwoo; Lee, Minbaek (Physica Status Solidi - Rapid Research Letters, 2020)
Recent transistors are one of state-of-the-art products of semiconductor industry. As it has been required to be minimized to the nanoscale regime, the classical model from the microelectronics is often challenged by its discrepancy. Therefore, understanding the behavior of electrons in such regime is essential for transistor applications in nanoscale. Herein, the charge trapping and anisotropic diffusion behaviors of electrons in multistacked nanostructures composed of a blocking oxide, a charge storage layer of Au nanoclusters (NCs), a tunneling oxide, and silicon substrate are reported. Electrons are injected from the substrate to Au NCs via quantum tunneling effect. The charge retention and diffusion characteristics of the NCs are investigated by measuring surface potential. To explore the spatial dependence, a line- and dot-shaped injection of charges is examined. Both of the accumulated electrons decay following an exponential function of time. However, the injected electrons with a line-shape in Au NCs are found to have a larger time constant than those with a dot-shape. This result implies that the initial spatial distribution of electrons plays a role in determining the equilibrium distribution of the charges in the nanostructure.
Keywords: Anisotropic Diffusion; Charge retention; Charge trap; Diffusion characteristics; Equilibrium distributions; Quantum tunneling; Quantum tunneling effects; Semiconductor industry; charge retention; charge traps; flash memories; nanoparticles; quantum tunneling